EMPIRICAL STUDY OF BRAND REGISTRATION AWARENESS BY UMKM - Destyarini, Normalita; Dwi Rahmawati, Nadila; Nur Annisa, Miftia (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2023)
The business sector can never escape intellectual property. Every business conducted must have intellectual property contained therein. Intellectual property in question can be in the form of trademarks for business actors. In order to protect the economic value of business actors which is a priority value for business actors. For this reason, it is important to socialize and provide guidance to the community of business actors in Surakarta City which is adjusted to the provisions of Law Number 30 of 2000 concerning Trade Secrets and Law Number 20 of 2016 concerning Trademarks and Geographical Indications. The output of the activity is in the form of scientific publications, integration in intellectual property law. courses and uploading videos of activities on the YouTube platform.